2020
DOI: 10.1002/acp.3674
|View full text |Cite
|
Sign up to set email alerts
|

Personality, confirmation bias, and forensic interviewing performance

Abstract: Summary Confirmation bias is a universal characteristic of human cognition, with consequences for information processing and reasoning in everyday situations as well as in professional work such as forensic interviewing. Cognitive measures such as general intelligence are also related to personality traits, but there is a lack of research on personality and confirmation bias specifically. This study focuses, firstly, on the relationship between Big Five personality traits and confirmation bias as measured by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Notwithstanding a brief guideline on the importance of only employing recommended (e.g., open-ended questions) and non-leading questioning techniques provided to the participants before the first interview, it seemed that only building hypotheses may unintentionally shape the questioning styles of interviewers in a negative direction leading to an increased number of non-recommended questions [ 44 , 82 , 83 ]. We were also interested in understanding whether learning questioning skills and the hypothesis-testing approach simultaneously introduced too much new information to the interviewers having a negative impact on their learning outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding a brief guideline on the importance of only employing recommended (e.g., open-ended questions) and non-leading questioning techniques provided to the participants before the first interview, it seemed that only building hypotheses may unintentionally shape the questioning styles of interviewers in a negative direction leading to an increased number of non-recommended questions [ 44 , 82 , 83 ]. We were also interested in understanding whether learning questioning skills and the hypothesis-testing approach simultaneously introduced too much new information to the interviewers having a negative impact on their learning outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Confirmation bias refers to a universal human tendency to look for and interpret evidence that is consistent with one’s prior beliefs [ 34 , 35 ]. Literature on information acquisition has clearly shown that people have a tendency to seek evidence confirming their initial belief [ 36 39 ], and to ignore information that goes against it [ 40 , 41 ], with potentially negative effects on professionals investigating CSA allegations [ 12 , 42 44 ]. Hence, pre-interview beliefs held by interviewers are central and may lead to confirmation bias, resulting in use of closed-ended questions [ 45 , 46 ] that may endanger the reliability of responses elicited from children and in extreme cases can make the interviewer arrive at an incorrect conclusion [ 47 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…If so, what distinguishes these individuals from those who stay more openminded? Besides some efforts investigating the role of Big Five personality traits in interviewing performance Melinder et al, 2020), scholars have mainly suggested cognitive and emotional factors as individual level influences on interviewer bias.…”
Section: Understanding Interviewer Bias As a Differential Constructmentioning
confidence: 99%
“…While this is an effective strategy in everyday life where heuristics help us in dealing with a huge amount of information, such confirmation bias can have deleterious effects in some contexts (Mynatt et al, 1977; Nickerson, 1998). This bias has also been examined in the legal and forensic settings, showing, for example, that trait confirmation bias was negatively associated with evaluator‐rated interview performance among police officers who were receiving interview training (Melinder et al, 2020). Compared with exonerating tactics, interrogators who presume the suspect to be guilty tend to use more guilt‐confirming tactics (Rassin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%